2007
DOI: 10.1108/14637150710752344
|View full text |Cite
|
Sign up to set email alerts
|

Business process reengineering: critical success factors in higher education

Abstract: Purpose-The purpose of this paper is to examine the critical success factors of business process reengineering (BPR) in higher education (HE). Design/methodology/approach-Empirical case studies collected from three private higher education institutions in Malaysia, which have embarked on BPR successfully. Findings-Seven factors were found to be critical to BPR implementation success. The factors are teamwork and quality culture, quality management system and satisfactory rewards, effective change management, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
133
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 37 publications
9
133
1
9
Order By: Relevance
“…Therefore having a less bureaucratic and more participative structure is essential for successful BPR implementation. This is parallel with McAdam [51] statement that organizations should apply a more participative structure to avoid failure of BPR implementation [46].…”
Section: E Less Bureaucratic Structure (Flatter Structure)mentioning
confidence: 77%
See 2 more Smart Citations
“…Therefore having a less bureaucratic and more participative structure is essential for successful BPR implementation. This is parallel with McAdam [51] statement that organizations should apply a more participative structure to avoid failure of BPR implementation [46].…”
Section: E Less Bureaucratic Structure (Flatter Structure)mentioning
confidence: 77%
“…BPR implementation is a costly process. Therefore, organizations should have adequate financial resources for implementing changes and facing with unpredictable situations [4], [8], [46].…”
Section: G Adequate Financial Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…While in the dynamic form, the leader actively monitors subordinates' performance and corrects any mistakes, in the passive form, the leader does not monitor but waits for mistakes to happen and then takes action. The employee can still be engaged with the change implementation not because they want to but because they have to, also supported by Ahmad et al (2007). In this situation, transactional leadership is expected to be associated with employee commitment to organisational change.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…how this type of leader affects his followers by motivation and satisfaction), but are not necessarily concerned with leadership as they relate to change or specifically how leaders affect change in people (House, 1996). Ahmad, Francis, & Zairi (2007) found that the different styles of leadership lead to different results, and drastic change required more autocratic style. The following section elaborates the two dominant styles of leadership more, namely; the transformational and transactional leadership.…”
Section: Leadership Stylementioning
confidence: 99%